Characteristics of anemia in heart failure: iron metabolism, erythropoietic activity and markers of inflammation - A. A. Gurkina; N. I. Stuklov; N. D. Kisly; R. R. Gimadiev; M. S. Kovalchuk (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To determine the characteristics of erythrocyte parameters, iron metabolism, erythropoiesis, inflammation markers in patients with heart failure (CHF) and anemia.Material and methods. The study included 68 patients with HF to describe the characteristics of anemia (general group). Patients of the general group were divided into 3 subgroups depending on the serum ferritin (SF) and transferrin saturation (TS).Results. Anemia in HF is not always associated with iron deficiency (ID), characterized by inadequate production of erythropoietin, increased levels of C-reactive protein and hepcidin. From the general group of patients, the following were distinguished: absolute ID (43%), functional ID (19%), and non-ID anemia (38%).Conclusion. In the general group of patients with HF, anemia is normochromic, normocytic, characterized by high levels of C-reactive protein, hepcidin, and inadequate production of erythropoietin. Patients with absolute and functional ID do not differ in the main iron metabolism parameters and in general account for 62% (p=0,01). In these two subgroups, iron supplements should be prescribed at further stages.